Scholarship’s Payment Modelling for Work Accident Insurance Program (JKK) in Indonesia - Yulial Hikmah (EKSAKTA: Journal of Sciences and Data Analysis, 2021)
Work Accident Insurance (JKK) is a protection for the risk of accidents or illness due to work during the service period. JKK is divided into two benefits, namely care and compensation. Undang-Undang Republik Indonesia No 102/2015 regulates that scholarship assistance is given in lump sum (at once). Giving lumpsum scholarship assistance is felt to be less on target. Some cases that have occurred, the recipient (heir) has not attended school when given scholarship assistance so it is probable that the scholarship assistance is not used properly. This study discusses 3 models, namely the lumpsum model based on Undang-Undang Republik Indonesia No 102/2015, alternative model 1 (Rp 30,000,000 and given when entering a new level of education), and alternative model 2 (Rp 40,000,000 and given when entering a new level of education). There are three criteria in determining the best model, which has a greater benefit value, the burden that must be borne by the company is smaller or the same as the lumpsum method and payment is more targeted. By using these three criteria, it was found that alternative model 2 was the best model.